The main important thing in health care professions: a clinician's reflections. - Lombardi, Domenico (Medicina e Morale, 2001)
The article dwells upon the reflections about principles and behaviours in health care professions. In Author's opinion adequate technical-scientific and ethical-cultural skills are necessary means to qualify the patient's care and maintain an a high-level of professionalism. The goals of the health care profession are discussed and also the quality of the life, that is closely connected to the health. Four parts are considered in the health care profession: physic, psychic, cognitive and volitive one, and some references for improving it are pointed out. The professional action is considered adequate when it is free and responsible, and the holistic approach is considered the most proportionate to approach the sick person, also for the specialist. Moreover, the development of the specialistic medicine and the actual validity of the "mother disciplines" (internal medicine and general surgery) are discussed. The requisites that qualify both the HCOs and the behaviours of the health care professionals are discussed. Regarding the social medicine, the principles that should regulate the health are showed, because health never has to become commodity of exchange. Finally, the essentiality of the fiduciary relationship between physician and patient is discussed. This therapeutic covenant should privilege, over that the professional skill of the doctor, also the human knowledge and the respect of the sick person in his/her somatic, psychic and spiritual ontological unity. Legal and ethical references that should drive the behaviours of health care professionals are illustrated.